The therapeutic potential of icariin in the intervention of bone and joint diseases through multiple pathways: a narrative review - Luo, Jiayi; Wu, Lijiao; Xu, Yunying; Zhang, Jingqi; Zhao, Xinyi; Wang, Xiangjin (Frontiers in Pharmacology, 2025)
The prevalence of bone and joint diseases is projected to increase owing to rapidly aging populations, sedentary lifestyles, and unhealthy diets. This poses a significant challenge for the global healthcare system. In recent years, natural herbal medicines have been used to treat various types of orthopedic diseases, opening new frontiers in new drug research. Epimedium is a traditional Chinese herb with a long history of medicinal use. It is commonly used to treat osteoporosis, joint disorders, cardiovascular diseases, sexual dysfunction and aging. The primary active component of Epimedium is icariin (ICA), an isoprenylated flavonoid. Recent studies have demonstrated its significant positive effects on bone metabolism and remodeling, including promoting osteoblast proliferation and mineralization, reducing osteoclast activity, and inhibiting inflammation and oxidative stress. Thus, ICA represents a potential compound for treating bone and joint diseases. However, the specific mechanisms underlying these effects have not yet been fully elucidated. This paper focuses on the latest advances in the use of ICA for the treatment of skeletal and joint diseases, covering a range of conditions including osteoporosis, osteoarthritis, rheumatoid arthritis, intervertebral disc degeneration and fractures. Building on this, we have systematically integrated its multi-target pharmacological mechanism network for the first time, elucidating its multi-pathway synergistic effects mediated by regulating the balance of the bone microenvironment. In summary, as a multi-target natural compound, ICA demonstrates significant translational medicine potential in the comprehensive treatment of bone and joint diseases, providing a critical theoretical foundation for the development of novel therapeutic strategies.